IMPACT OF WORK LIFE BALANCE OF FEMALE CREW ON JOB SATISFACTION - B, Muralikrishnan; B, Vimala (International Journal of Psychosocial Rehabilitation, 2019)
The article tries to identify theimpact of work life balance of female crew onjob satisfaction. Pilot study sample size was 50 female crew members. This research has employed simple random sampling technique to collect data from female crew.The analysis discovered the work interference with personal life and personal life interference with work not influences on job satisfaction among female crew.The analysisalso identified the work/personal life enhancement influences job satisfaction among female crew.It is found the work/personal life enhancement influences life satisfaction among female crew.The analysis also revealed the work life balance influences life satisfaction among female crew.Hence, it is concluded that the aviation industryadministrators that the work and family related issues can be minimized by managing the time schedules of the female crew. If work and family related issues is minimized of work life balance can be boosted.